Oxygen-Ozone Treatment in Bisphosphonate Related Osteonecrosis of the Jaw: A Case Report - Cicconetti A; Passaretti A; Zuccarini F; Tordiglione P; Araimo Morselli FSM; Imperiale C; Miracolo G (Global Journal of Anesthesiology - Peertechz Publications, 2016)
The bisphosphonate related osteonecrosis of the jaws (BRONJ) is defined as a drug-adverse reaction that involves the maxillary bones.  It develops during or after a long-term bisphosphonate therapy in absence of radiotherapy [1]. The clinical pattern was described for the first time by Marx RE in 2003, who observed the development of jaws osteonecrosis in patients underwent to Multiple Myeloma and Mammary Cancer therapy [2]. Bisphosphonates (BF) pharmacokinetics consist in the osteoclast function interruption, angiogenesis inhibition, as well as blocking any cancer cell line activity together with the interruption of signal transduction [3]. In this way the bone regeneration is interrupted and osteonecrosis is more probable.